ANALYSIS OF INDIGENOUS LITERATURE WITH SPECIAL REFERENCE TO INDIA, CANADA AND NEPAL - Dr. Prem Bahadur Khadka (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
Beginning with a meaning of indigenous people groups as the first or common occupants of a nation or locale, one may portray indigenous writing as writing created by unique or local people groups and their relatives. Writing can take numerous structures: verse, show, fiction, and innovative verifiable. Diaries and self-portraying compositions are of specific significance as a type of verifiable that can give social setting to the translation and comprehension of indigenous writing.